2019
DOI: 10.1108/jmtm-08-2017-0159
|View full text |Cite
|
Sign up to set email alerts
|

Structural equation modeling of lean manufacturing practices in a developing country context

Abstract: Purpose The purpose of this paper is to empirically examine lean manufacturing (LM) practices and to quantify their impact on business performance (BP), with particular emphasis on the mediating role of operational performance (OP) in deriving the BP benefits commonly linked with LM. It also seeks to identify those lean practices most appropriate for application. Design/methodology/approach Empirical data on LM practices were collected using a structured survey questionnaire. The sampling frame was Jordanian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 71 publications
(96 reference statements)
2
53
0
1
Order By: Relevance
“…Zahraee [69] found that processes and equipment, planning and control, human resources, supplier relationships, and customer relations are significant practices for LM. Shrafat [70] recommended a LM framework for developing countries comprised of housekeeping 5s, single minute exchange of dies, total preventive maintenance, supplier just-in-time, pull production, continuous flow, and statistical process control. In this research, LM measures proposed by [5,11,71,72] were applied to frame the LM, construct consisting of purchasing and distribution, production, facility, and quality.…”
Section: Survey Instrumentmentioning
confidence: 99%
“…Zahraee [69] found that processes and equipment, planning and control, human resources, supplier relationships, and customer relations are significant practices for LM. Shrafat [70] recommended a LM framework for developing countries comprised of housekeeping 5s, single minute exchange of dies, total preventive maintenance, supplier just-in-time, pull production, continuous flow, and statistical process control. In this research, LM measures proposed by [5,11,71,72] were applied to frame the LM, construct consisting of purchasing and distribution, production, facility, and quality.…”
Section: Survey Instrumentmentioning
confidence: 99%
“…Researchers such as Eswaramoorthi et al, 15 Khanchanapong et al, 22 Nawanir et al 24 and Marodin et al 53 have shown that the adoption of LM has given manufacturing companies a competitive edge through yielding positive results. Shrafat and Ismail 106 concluded that limited research has been conducted on LM in developing countries. Marodin et al 53 stated that developed countries often face difficulties to become Lean due to the changes in the market orientation.…”
Section: Discussionmentioning
confidence: 99%
“…However, we argue that lean manufacturing principles are primarily grounded on the philosophy of maximizing productivity by minimizing the ordeal of industrial waste ( Botti et al., 2017 ; Cortez et al., 2020 ; Maia et al., 2019 ; Thomas et al., 2018 ). Furthermore, we assert that although industrial waste can be minimized by implementing the lean manufacturing principles ( Andrade et al., 2020 ; Chauhan, 2016 ; Manfredsson, 2016 ; Shrafat and Ismail, 2019 ). Yet, the essence of organizational concern towards environment protection is much noteworthy in CPP ( Aranda-Usón et al., 2020 ; Cesar da Silva et al., 2021 ; de Oliveira et al., 2019 ; Ramos et al., 2021 ; Scarazzato et al., 2017 ) which makes former significantly less industrious in terms of our environmental safeguard measures ( Botti et al., 2017 ; Cong and Shi, 2019 ; Psomas and Antony, 2019 ; Salam and Farooq, 2020 ).…”
Section: Introductionmentioning
confidence: 91%